Distinguishing Characteristic of the Industrial Development of the South of Russia (Kuban and Stavropol) at the Turn of the 1920-1930s - D. A. Salfetnikov (Научный диалог)
The question of the development of the Kuban and Stavropol economy industrial sectors in the years of the initial stage of the industrialization plans is considered. The results of a comparative analysis of the industrial sectors of these agricultural regions in their production ratio with the agricultural sector are presented. The relevance of the study is due to the need to analyze the factors of economic interrelation of various business entities, as well as regional characteristics of economic development based on an integrated approach when analyzing the socio-economic transformations of this period. The novelty of the research is in the fact that the economic situation in these agrarian southern Russian regions is being reconstructed from the point of view of the tasks of industrial development and the effectiveness of their solution in the historical context of the corresponding epoch. Special attention is paid to the issues of interaction in this period of collectivized agriculture with industry, primarily with its two branches - food and processing. The problems of reconstruction of relevant enterprises and the construction of new plants and factories are touched upon. Their classification by industry and degree of importance is proposed. It is proved that the industrial enterprises of Stavropol and, especially, Kuban were distinguished by a multi-vector application and development of their production potential, despite the pronounced agrarian dominant in the economy of these regions.